User-generated content strategy & millennials’ travel intentions - Almeida, Constança Garcez Palha Moitinho de (2019)
Instagram has created new exciting ways for millennials to connect, interact and contribute to a pool of online content by taking on the role of content creators. Hence, millennials’ experiences are being shaped by information obtained and created online in the form of User-Generated Content (UGC). However, recent tactics to integrate UGC within brands’ content strategies raised questions about the effects of ‘pure’ UGC compared to other UGC tactics (e.g. paid partnership or sponsored content). The main goal of the study was to understand how exposure to different User-Generated Content Strategies influence millennials’ decisions in the context of Instagram and Travel. In order to achieve these goals, a cross-sectional online survey with a built-in experiment was conducted. Findings from the quantitative data analysis indicated that travel-related UGC created on Instagram shapes every stage of Millennials’ Travel Journeys. In addition, results showed significant differences in the degree of Millennials’ Online Engagement, Perceived Trustworthiness, and Travel Intentions, when exposed to different strategies of UGC. Moreover, UGC created by an independent Instagram user showed the most significant results in terms of Engagement. However, when it came to Trustworthiness, UGC #reposted on a Brand Official Account turned out to be the best strategy to gain Millennials’ Trust. This study further emphasizes the valuable potential of UGC for businesses and contributes to relevant insights and practical recommendations on how marketers can take advantage of UGC as a marketing tool and develop an effective UGC Strategy to target Millennials.